Effects of replacing Na selenite in laying hen feed with selenized glucose on production performance, egg quality, egg selenium content, microbial population, immunological response, antioxidant enzymes, and fatty acid composition - Farimah Mohammadsadeghi; Mohsen Afsharmanesh; Mohammad Salarmoini; Mohammad Khajeh Bami (Poultry Science, 2024)
ABSTRACT: This study aimed to explore the effects of selenized glucose (SeGlu) and Na selenite supplementation on various aspects of laying hens such as production performance, egg quality, egg Se concentration, microbial population, antioxidant enzymes activity, immunological response, and yolk fatty acid profile. Using a 2 × 2 factorial design, 168 laying hens at 27-wk of age were randomly divided into 4 treatment groups with 7 replications. Se source (Na selenite and SeGlu) and Se level (0.3 and 0.6 mg/kg) were used as treatments. When 0.3 mg SeGlu/kg was compared to 0.3 mg Na selenite/kg, the interaction findings revealed that 0.3 mg SeGlu/kg increased egg production percent and shell ash (P < 0.05). When compared to 0.3 mg Na selenite/kg, dietary supplementation with 0.3 and 0.6 mg SeGlu/kg resulted in an increase in albumen height, Haugh unit, and yolk color of fresh eggs (P < 0.05). SeGlu enhanced albumen height, Haugh unit, shell thickness (P < 0.01), albumen index, yolk share, specific gravity, shell ash (P < 0.05) of fresh eggs and shell thickness (P < 0.05) of stored eggs as compared to Na selenite. The interaction showed that 0.6 mg SeGlu/kg enhanced yolk Se concentration while decreasing malondialdehyde levels in fresh egg yolk (P < 0.05). SeGlu enhanced Se concentration in albumen and glutathione peroxidase activity in plasma (P < 0.05) as compared to Na selenite. 0.6 mg Se/kg increased lactic acid bacteria, antibody response to sheep red blood cells, and lowered ∑n-6 PUFA/ ∑n-3 PUFA ratio (P < 0.05). As a result, adding SeGlu to the feed of laying hens enhanced egg production, egg quality, egg Se concentration, fresh yolk lipid oxidation, and glutathione peroxidase enzyme activity.